An injectable poly(caprolactone trifumarate-gelatin microparticles) (PCLTF-GMPs) scaffold for irregular bone defects: Physical and mechanical characteristics - Al-Namnam, N.M.; Kutty, Muralithran Govindan; Chai, Wen Lin; Ha, K.O.; Kim, K.H.; Siar, Chong Huat; Ngeow, Wei Cheong (Elsevier, 2017)
Recently, a modified form of a three-dimension (3D) porous poly(caprolactone-trifumarate) (PCLTF) scaffold has been produced using a fabrication technique that involves gelatin microparticles porogen leaching. This poly(caprolactone trifumarate-gelatin microparticles) (PCLTF-GMPs) scaffold has been shown to be biocompatible, more flowable clinically, and has a shorter degradation time as compared to its existing predecessors. In this report, a detailed characterization of this new scaffold was performed by testing its cytocompatibility, analyzing the surface topography, and understanding its thermal, physical and mechanical properties. The result showed that the PCLTF-GMPs has no critical cytotoxic effect. To confirm improvement, the surface properties were compared against the older version of PCLTF fabricated using salt porogen leaching. This PCLTF-GMPs scaffold showed no significant difference (unpaired t-test; p > 0.05) in mechanical properties before and after gelatin leaching. However, it is mechanically weaker when compared to its predecessors. It has a high biodegradability rate of 16 weeks. The pore size produced ranges from 40 to 300 mu m, and the RMS roughness is 613.7 +/- 236.9 nm. These characteristics are condusive for osteoblast in-growth, as observed by the extension of filopodia across the macropores. Overall, this newly produced material has good thermal, physical and mechanical properties that complements its biocompatibility and ease of use. (C) 2016 Elsevier B.V. All rights reserved.